Union organization in Great Britain - Willman, Paul; Bryson, Alex (London, 2007)
"Union membership and density in Britain has experienced substantial decline since 1979. The fall in private sector membership and density has been much greater than in the public sector. The size of the union sector, measured by employer recognition, has shrunk. Membership decline has been accompanied by financial decline. Much of the decline occurred before 1997, under Conservative governments. Since 1997 and the return of a Labour government, the position has in some respects stabilized. Currently, unions have a substantially reduced economic impact, but a continued, if limited, role in workplace communication and grievance handling, often as part of a voice regime including non union elements."